ON THE ESSENTIAL SPECTRUM OF A QUADRATIC OPERATOR MATRIX OF ORDER 4 - Rasulov, Tulkin (Journal of Global Research in Mathematical Archives(JGRMA), 2019)
In the present paper, we precisely describe the location of the essential spectrum of a quadratic operator matrix A4 of order 4 associated to a system describing four particles in interaction, without conservation of the number of particles, in the quasi-momentum representation. It is also established that the essential spectrum of A4 consists of no more than seven bounded closed intervals.